Extracellular Matrix Disparities in an Nkx2-5 Mutant Mouse Model of Congenital Heart Disease - Bousalis, Deanna; Lacko, Christopher S.; Hlavac, Nora; Alkassis, Fariz; Wachs, Rebecca A.; Mobini, Sahba; Schmidt, Christine E.; Kasahara, Hideko (Frontiers in Cardiovascular Medicine, 2020)
Congenital heart disease (CHD) affects almost one percent of all live births. Despite diagnostic and surgical reparative advances, the causes and mechanisms of CHD are still primarily unknown. The extracellular matrix plays a large role in cell communication, function, and differentiation, and therefore likely plays a role in disease development and pathophysiology. Cell adhesion and gap junction proteins, such as integrins and connexins, are also essential to cellular communication and behavior, and could interact directly (integrins) or indirectly (connexins) with the extracellular matrix. In this work, we explore disparities in the expression and spatial patterning of extracellular matrix, adhesion, and gap junction proteins between wild type and Nkx2-5+/R52G mutant mice. Decellularization and proteomic analysis, Western blotting, histology, immunostaining, and mechanical assessment of embryonic and neonatal wild type and Nkx2-5 mutant mouse hearts were performed. An increased abundance of collagen IV, fibronectin, and integrin β-1 was found in Nkx2-5 mutant neonatal mouse hearts, as well as increased expression of connexin 43 in embryonic mutant hearts. Furthermore, a ventricular noncompaction phenotype was observed in both embryonic and neonatal mutant hearts, as well as spatial disorganization of ECM proteins collagen IV and laminin in mutant hearts. Characterizing such properties in a mutant mouse model provides valuable information that can be applied to better understanding the mechanisms of congenital heart disease.